2015
DOI: 10.1051/limn/2014028
|View full text |Cite
|
Sign up to set email alerts
|

An eco-hydrological assessment method for temporary rivers. The Celone and Salsola rivers case study (SE, Italy)

Abstract: -This paper presents the results of a study which characterizes the hydrological regime of a temporary river at reach scale and analyzes the hydrological alterations due to anthropogenic pressures using the SWAT model to estimate the daily streamflows and the periods without flow which would occur in natural conditions. The study area is the Salsola and Celone river basins, located in SE Italy. In a first part, we identified six classes of flow, the so-called Aquatic States (ASs), which play a major role in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…In the present study, among the large number of hydrological variables extracted from streamflow data, a small number of uncorrelated variables were identified via PCA. As the hydrological regimes of temporary rivers are quite specific (De Girolamo et al ., ), it is expected that the HIs representing the major facets of these regimes are different from those for perennial rivers. Hence, we performed the PCA for all rivers and also differentiated the rivers into two sets identified a priori : perennial and temporary.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, among the large number of hydrological variables extracted from streamflow data, a small number of uncorrelated variables were identified via PCA. As the hydrological regimes of temporary rivers are quite specific (De Girolamo et al ., ), it is expected that the HIs representing the major facets of these regimes are different from those for perennial rivers. Hence, we performed the PCA for all rivers and also differentiated the rivers into two sets identified a priori : perennial and temporary.…”
Section: Discussionmentioning
confidence: 99%
“…While habitat availability for lotic and lentic species increases with perennialization, habitat availability for terrestrial and semi-aquatic species declines. Although perennial flow may be sustained by effluent discharge, pollution can be detrimental for aquatic assemblages, as BOD 5 , dissolved oxygen, and nutrient concentrations frequently exceed the threshold of "good" water quality due to limited dilution (De Girolamo et al, 2015a). Also, in artificially sustained perrenial stream streches downstream of dams, a spread of alien fish species has been observed in many insular basins where NPSR dominate, such as in Corsica, Cyprus and Sicily among other Mediterranean islands (Blondel et al, 2010;Zogaris et al, 2012).…”
Section: Ecological Impactsmentioning
confidence: 99%
“…For example, Kirkby et al (2011) addressed the relative frequency of ecologically critical low flow stages in semiarid rivers across Europe. Moreover, using modeling approaches, it has been shown that entire river reaches may dry out as a result of water abstraction for agriculture De Girolamo et al, 2015a). Thus, De Girolamo et al (2015b) developed a new approach for evaluating the hydrological status of NPRS, in which the divergence between the current (impacted) and the natural flow conditions are assessed by using two hydrological indicators; the long-term annual mean number of months with flow (MF) , and the six-month seasonal predictability of dry periods (SD6) (Gallart et al, 2012).…”
Section: Hydrological Processesmentioning
confidence: 99%
“…hydrology, ecology and chemistry) of temporary streams [e.g. Dieter et al ., ; García‐Roger et al ., ; Kirkby et al ., ; Gallart et al ., ; De Girolamo et al ., , (submitted)]. The main focus of the MIRAGE Toolbox is to help professionals addressing the management of temporary streams from an interdisciplinary perspective by covering a wide range of the conditions that a temporary stream may experience.…”
Section: Introductionmentioning
confidence: 97%